Biased transformation erases traditions sustained by conformist transmission - Morgan, Thomas J. H. (Biol Lett, 2020)
Conformist transmission is a cognitively simple decision-making process by which observers are disproportionately likely to follow the majority. It has been studied in multiple species because theory suggests it can create stable cultural variation. However, the current theory assumes that while conformist transmission favours the majority, it is otherwise unbiased and does not systematically transform information, even though such biases are widely documented. Here, we relax this assumption, requiring conformist observers to infer the size of the majority from finite observations of their group mates. Because such inference can be subject to bias, it can lead to the biased transformation of transmitted information. We find that when individuals are biased (even weakly) the capacity of conformist transmission to sustain traditions is reduced and, in many cases, removed entirely. This suggests that the emphasis on conformist transmission as a source of stable cultural variation may be misplaced.